2019
DOI: 10.1109/access.2019.2910660
|View full text |Cite
|
Sign up to set email alerts
|

Leakage Current Response Mechanism of Insulator String With Ambient Humidity on Days Without Rain

Abstract: The leakage current, which is influenced by the operating voltage, the surface contamination, and environmental variables, is one of the most basic online monitoring parameters for the surface contamination status of insulators. However, the impact of temperature and humidity on leakage current have not been expressed concisely nor distinguished according to sunny and rainy weather. In this paper, based on leakage current online monitoring data, the time-domain waveforms of leakage current of an insulator stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 13 publications
12
20
0
Order By: Relevance
“…Content may change prior to final publication. In addition, this case was in line with [10,12,15,17,18,26] because the rise in the local time occurred between 04:00 and 08:00. According to Pieterse et al [10], it occurred on the relatively low creepage distance of 615 mm, rather than the high creepage distance of 1175 mm.…”
Section: Figure 3sample Waveforms Of the Jpeg Picturesupporting
confidence: 79%
See 2 more Smart Citations
“…Content may change prior to final publication. In addition, this case was in line with [10,12,15,17,18,26] because the rise in the local time occurred between 04:00 and 08:00. According to Pieterse et al [10], it occurred on the relatively low creepage distance of 615 mm, rather than the high creepage distance of 1175 mm.…”
Section: Figure 3sample Waveforms Of the Jpeg Picturesupporting
confidence: 79%
“…-0.90 to -1.00 (0.90 to 1.00) Very high negative (positive) correlation Generally, the data on one parameter were not inherently linear to the asymptotic patterns on the other parameters. Therefore, exponential models were employed to determine the regressions [12,[23][24], as shown in equation 4, where C and D are the constant and exponential constant of the regression, respectively.…”
Section: Size Of Correlation Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, the online measurements of LCVS, from the insulator, are required to be fed to the MNN which is trained to recognize the contamination type using LCVs. However, online translation of surface leakage current measurements of insulators is still open to research [39,40]. Therefore, in the present work, pre-measured LCVs (experimental measurements, 18 × 5 = 90) were used and encoded with the MNN.…”
Section: A Proposed Fcn Architecturementioning
confidence: 99%
“…A reasonably high correlation is observed (coefficient of determination ≈ 0.6), though the correlation drops in highly polluted insulators. In [13], the leakage current in insulator strings is correlated against temperature and ambient humidity in a 110 kV system. It is observed that the leakage current exhibits a positive correlation with RH (coefficient of determination > 0.8) and a negative correlation with temperature.…”
Section: Previous Workmentioning
confidence: 99%